On Central Closure of Totally Prime Algebras (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
Seemingly, it is not easy to finding a norm on the center closure of a normed algebra. Cabrera and Mohammed in [1,2], they defined a norm on the center closure of two classes of algebras namely totally multiplicatively prime and associative totally prime algebras. In this paper, we prove the same result in a general setting by considering the class of non-associative totally prime algebras which have a prime multiplication algebra.